Pediatric Vital Sign Distribution Derived From a Multi-Centered Emergency Department Database - Sepanski, Robert J.; Godambe, Sandip A.; Zaritsky, Arno L. (Frontiers in Pediatrics, 2018)
Background: We hypothesized that current vital sign thresholds used in pediatric emergency department screening tools do not reflect observed vital signs in this population. We analyzed a large multi-centered database to develop heart rate and respiratory rate centile rankings and z-scores that could be incorporated into electronic health record emergency department screening tools and we compared our derived centiles to previously published centiles and Pediatric Advanced Life Support vital sign thresholds. Methods: Initial heart rate and respiratory rate data entered into the Cerner™ electronic health record at 169 participating hospitals’ emergency departments over five years (2009 through 2013) as part of routine care were analyzed. Analysis was restricted to non-admitted children (0 to <18 years). Centile curves and z-scores were developed using Generalized Additive Models for Location, Scale, and Shape. A split-sample validation using two-thirds of the sample was compared with the remaining one-third. Centile values were compared with results from previous studies and guidelines. Results: HR and RR centiles and z-scores were determined from ~1.2 million records. Empirically-derived 95th centiles for heart rate and respiratory rate were higher than previously published results and both deviated from Pediatric Advanced Life Support guideline recommendations. Conclusions: Heart and respiratory rate centiles derived from a large real-world non-hospitalized emergency department pediatric population can inform the modification of electronic and paper-based screening tools to stratify children by the degree of deviation from normal for age rather than dichotomizing children into groups having “normal” versus “abnormal” vital signs. Furthermore, these centiles also may be useful in paper-based screening tools and bedside alarm limits for children in areas other than the ED and may establish improved alarm limits for bedside monitors.